Early Clinical Experience with Double Ring Implantation for Aortic and Mitral Valve Repair - Russo, M.; Andreas, M.; Rankin, S. J.; Maisano, F.; Weber, A. (The Thoracic and Cardiovascular Surgeon, 2019)
Reconstruction of cardiac valves is associated with reduced mortality, including in multiple valve surgery. However, multiple valve repair is still considered a challenge, even with established techniques. Recently, internal aortic ring annuloplasty has been introduced and could simplify multiple valve reconstruction. This study reports early results with double ring aortic and mitral valve repair. Three patients with bivalvular degenerative regurgitation were managed with combined aortic and mitral valve repair using double rings. Mean (±SD) age was 41 ± 21 years, preoperative left ventricular end-diastolic volume was 119 ± 53 mL/m2, and ejection fraction was 0.50 ± 0.07. Mean aortic ring diameter was 21 mm, and mitral rings averaged 32 mm. No operative mortalities or major complications were observed. No valve-related events occurred. Postoperative echo showed complete resolution of mitral and aortic regurgitation. Postoperative left ventricular end-diastolic volume decreased to 98 ± 10 mL/m2; no left ventricular outflow tract obstruction or significant transvalvular gradients were observed. Postoperative cardiac CTs showed an optimal three-dimensional configuration of aortic and mitral annuloplasty devices. This initial series demonstrated the feasibility and safety of combined aortic and mitral repair with double rings. Clinical and hemodynamic results were promising. Increasing application and more clinical experience with combined aortic and mitral double ring repair seems indicated.
Keywords: aortic valve repair; mitral valve repair; ring implantation